(untitled) (Asian Education Studies, 2023)
The Government of Kenya (GoK) touts teacher-preparedness as a critical factor that shows the equipping of a professional teacher for quality performance and satisfactory learner performance in national examinations. Despite the efforts by the GoK, there is a worrying trend of students completing school with reading and writing difficulties. The Kenya National Examinations Council (2020) contends students‟ poor performance in English for the past 5 years, falling short of the average mean of 50%. Descriptive research design was used. A sample of 44 principals, 88 teachers and 345 form three students across 50 public secondary schools in Kakamega North, were targeted. A questionnaire, interview schedule, classroom practice observation schedule, and focus group discussion guide were used to collect data. Qualitative data was analyzed thematically whereas quantitative data was presented through tables, percentages and frequencies. Chi-square test was performed to test hypothesis. Response rate was 79.5%. The findings indicated that majority (97.1%) of the teachers participated in coursebooks and other revision textbook in-service courses as per the changing trends in teaching of English whereas ICT workshops had low percentages, a gap pointing on teacher level of preparedness. The findings from principals indicated, teachers of English sometimes declined to take up ICT in-service trainings for fear of additional responsibilities in school. Findings from FGDs show, teachers were rated average by most students in terms of preparedness in material use in classrooms. On determining the extent to which teacher level of preparedness influence implementation of English curriculum in school, teachers‟ opinions had a Mean of 4.0000; Standard deviation of 3.08338; and Skewness of .397, indicating teacher level of preparedness has a high and strong positive influence on implementation of English curriculum in school if well checked and applied. The study established a significant relationship between teacher level of preparedness and implementation of English curriculum (p=0.007<0.05). Findings concur with KNEC (2020), contending students‟ poor performance in English as unsatisfying.